Electrical and mechanical properties of nanometer-thick polypyrrole/polyglycerol films and nanomembranes - Balser, Sebastian; Zhao, Zhiyong; Liu, Yangbiao; Zharnikov, Michael; Terfort, Andreas (ACS applied nano materials, 2025)
As recently demonstrated, polymer films that are both biorepulsive and electrically conductive can be produced by electropolymerization of a polyglycerol-modified pyrrole derivative. In this work, we demonstrate that, in contrast to previous assumptions, the polypyrrole chains do not grow linearly, but are cross-linked, as the films could be lifted off the electrodes without disintegration. This cross-linking, which presumably proceeds via α-β and β-β linkages, not only opens new applications, but also requires an additional characterization of the films. To this end, several thickness-dependent parameters are characterized, starting from a minimal film thickness of 15.5 nm up to 132 nm. The evolution in chemistry during the film growth was monitored by X-ray photoelectron spectroscopy, showing characteristic changes. Measurements of the transversal electrical resistivities in two-terminal junctions suggest an Ohmic type of conductance, even though with a comparably low conductivity of (2.5 ± 1.2) × 10-8 S/m, which is ascribed to the dominance of the poorly conductive polyglycerol moieties in the bulk of the polymer network. As the polymer films could be lifted off from the substrates and mounted as free-standing membranes over a macroscopic window, the mechanical properties of the films could be characterized by bulge test experiments. These membranes show an elastic deformation at low pressures, followed by inelastic deformation at higher pressures. The Young’s moduli for the elastic range were estimated at 31-45 MPa, increasing progressively with the membrane thickness. The biorepulsive and conductive polyglycerol-pyrrole films and membranes are a useful addition to the pool of biomaterials.